PENGARUH BUDAYA ORGANISASI, MOTIVASI KERJA DAN GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN DI SATUAN KERJA PUSAT SISTEM DAN STRATEGI KESEHATAN KEMENTRIAN KESEHATAN REPUBLIK INDONESIA - Wujarso, Riyanto; Arifah, Assyfa Furi; Dewi, Sita; Listyowati, Dwi; Napitupulu, Bertha Elvy; Saragih, Rudy Hedianton (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Job satisfaction can affect work. Job satisfaction is related to how well employees' personal expectations at work match the results achieved. Job satisfaction is a subjective condition, formed based on a comparison between what employees receive from their work and what they expect, desire, or consider appropriate to receive. Employee job satisfaction is influenced by organizational culture, work motivation, and leadership style. The purpose of this study is to determine the effect of organizational culture, work motivation, and leadership style on the job satisfaction of PASSKAS employees, both partially and simultaneously. With a sample of 101 PASSKAS employees, use regression and correlation analysis, the results of this study show that, partially, organizational culture has a significant effect on the job satisfaction of PASSKAS employees. Work motivation partially has a significant effect on PASSKAS employee job satisfaction, and leadership style partially has a significant effect on PASSKAS job satisfaction. Simultaneously, organizational culture, work motivation, and leadership style have a significant effect on PASSKAS employee job satisfaction